2022
DOI: 10.3390/jrfm15070306
|View full text |Cite
|
Sign up to set email alerts
|

Does Board Gender Diversity Really Improve Firm Performance? Evidence from Greek Listed Firms

Abstract: In recent decades, the contribution of board gender diversity to corporate performance has drawn the interest of researchers, politicians and regulators. This paper examines whether board gender diversity affected the financial performance of 111 Greek listed firms from 2008 to 2020. We use the two-step system GMM estimator to address the endogeneity problem, which is the appropriate method used in governance literature. Our main empirical finding supports the existence of a positive relation between board gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
1
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 50 publications
5
20
1
5
Order By: Relevance
“…By investigating this underexplored research question, we contribute to a more comprehensive and nuanced understanding of the complexities at play. Our results challenge the notion that the relationship between gender diversity and firm performance can be universally generalized across all institutional settings (Brahma et al, 2021;Arvanitis et al, 2022;Gharbi and Othmani, 2022). Instead, we emphasize the critical importance of considering the variations in cultural norms, legal frameworks and social contexts that shape the dynamics within each context (Jayachandran, 2021;Koburtay et al, 2023).…”
Section: Theoretical Implicationscontrasting
confidence: 74%
“…By investigating this underexplored research question, we contribute to a more comprehensive and nuanced understanding of the complexities at play. Our results challenge the notion that the relationship between gender diversity and firm performance can be universally generalized across all institutional settings (Brahma et al, 2021;Arvanitis et al, 2022;Gharbi and Othmani, 2022). Instead, we emphasize the critical importance of considering the variations in cultural norms, legal frameworks and social contexts that shape the dynamics within each context (Jayachandran, 2021;Koburtay et al, 2023).…”
Section: Theoretical Implicationscontrasting
confidence: 74%
“…The association between BGD and firm performance has been excessively studied in previous literature, but the reached results were mixed. Several previous works, namely, Jiang et al (2020), EmadEldeen et al (2021, Arvanitis et al (2022), Brahma et al (2022), Fahad et al (2022) and Fayyaz et al (2022), showed that gender diversity is positively related to firm performance. This positive association confirms that women directors improve the effectiveness of boards based on their innovation and creativity regarding problem-solving, thus enhancing corporate performance.…”
Section: Bgd and Financial Performancementioning
confidence: 91%
“…To increase women's representation in boardrooms, countries such as Germany, Norway, Spain, France, Iceland, Italy, Belgium, Finland and Kenya have passed a legislative quota requiring firms to appoint between 30% and 40% of women to corporate boards (Brahma et al , 2022; Arvanitis et al , 2022). In contrast, the UK has adopted a voluntary approach against the quota-based approach.…”
Section: Introductionmentioning
confidence: 99%
“…Using Chinese-listed companies from 2010 to 2016, the results show that companies with a critical mass of at least three female board members have both high quality and faster implementation of environmental measures. Some of the studies show that the positive effect of women executives on performance turns into a negative effect after a certain critical point; almost 20% women board members (Nguyen et al, 2020) and a critical point of 33% women board members (Arvanitis et al, 2022). Fern andez-Temprano and Tejerina-Gaite (2020) look at Spanish nonfinancial companies and find no evidence of a possible impact of gender diversity on performance.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%